A potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment and a preparation method thereof

By incorporating specific dopants and sintering aids into potassium sodium niobate ceramics, a potassium sodium niobate-based piezoelectric ceramic suitable for low-temperature environments was prepared, which solved the problem of instability of existing ceramics in low-temperature environments. , and realize environmentally friendly high-performance ceramic materials.

CN118515481BActive Publication Date: 2025-01-24SOUTHWEST UNIVERSITY FOR NATIONALITIES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410642235.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-01-24
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

Existing piezoelectric ceramic materials show unstable piezoelectric properties in low temperature environments, which cannot meet the application needs of electronic equipment in high-altitude areas. At the same time, due to the content of lead elements, it is not conducive to environmental protection.

Method used

By doping Sb5+ into potassium sodium niobate ceramics, Bi0.5Ag0.5ZrO3 and NaSbO3 are chemically doped, and Fe2O3 is added as a sintering aid to prepare a potassium sodium niobate-based piezoelectric ceramic suitable for low-temperature environments. Its general chemical formula is: (0.984-x)K0.48Na0.52Nb0.95Sb0.05O3-xBi0.5Ag0.5ZrO3-0.016NaSbO3-0.4%Fe2O3.

Benefits of technology

The ceramic exhibits stable and excellent piezoelectric constants, electromechanical coupling coefficients and quality factors at room and low temperatures. The change rate of the piezoelectric constant is less than 25%, the change rate of the electromechanical coupling coefficient is less than 10%, and the change rate of the quality factors is less than 25%. Less than 5% and containing no lead, it is suitable for electronic sensing equipment in alpine regions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515481B_ABST
    Figure CN118515481B_ABST
Patent Text Reader

Abstract

The invention discloses a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment and a preparation method thereof, belonging to the field of piezoelectric ceramics. The potassium sodium niobate-based piezoelectric ceramic has a chemical formula of: (0.984-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3‑xBi 0.5 Ag 0.5 ZrO3‑0.016NaSbO3‑0.4%Fe2O3, where x is Bi 0.5 Ag 0.5 The present invention adopts the potassium sodium niobate-based piezoelectric ceramic suitable for low-temperature environments and the preparation method thereof, and exhibits stable and excellent piezoelectric constants, electromechanical coupling coefficients, and quality factors at room temperature and low temperature ranges, that is, the change rate of the piezoelectric constant is less than 25%, the change rate of the electromechanical coupling coefficient is less than 10%, and the change rate of the quality factor is less than 5%, and does not contain lead elements, and is an environmentally friendly material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric ceramics, and in particular to a potassium sodium niobate-based piezoelectric ceramic suitable for low-temperature environments and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics are a type of high-tech new material that can realize the mutual conversion between electricity and force, and therefore have become an indispensable key material in the fields of electronic information, artificial intelligence, medical health, etc. As a key component of electronic devices, piezoelectric ceramics are not only required to have a strong piezoelectric effect, but also to have excellent temperature stability and be able to be used in a wide operating temperature range.

[0003] Among them, lead zirconate titanate (PZT)-based ceramics have always dominated the global piezoelectric material market due to their excellent piezoelectric properties and temperature stability. However, lead-based piezoelectric ceramics contain a large amount of toxic lead elements, which are not conducive to environmental protection. Countries around the world have successively issued relevant laws to restrict the use of lead elements. Therefore, it is urgent to develop environmentally friendly lead-free piezoelectric materials with excellent performance to promote the process of lead-free electronic products.

[0004] Potassium sodium niobate (KNN)-based ceramics have excellent piezoelectric properties and high Curie temperature, making them one of the most promising options to replace lead-based piezoelectric materials. In recent years, researchers have conducted in-depth and extensive research on them and found that their piezoelectric properties can be effectively improved by constructing a new phase boundary at room temperature. Based on this, methods to improve their temperature stability include expanding the phase transition temperature region, constructing a multilayer structure with a component gradient, optimizing the preparation process, and other strategies, and have effectively improved the temperature stability of piezoelectric performance at room temperature and above. In particular, constructing a multiphase coexistence structure in the corresponding temperature range can effectively improve the piezoelectric performance in this temperature range.

[0005] It can be seen that the commercial ceramics on the market and researchers at home and abroad are mainly concerned with piezoelectric performance at room temperature and above, which can meet most application scenarios on the market. However, there are high-cold and humid areas both at home and abroad, which are in a low-temperature environment all year round. The application of electronic equipment in this area puts new requirements on the working temperature of related piezoelectric materials, that is, excellent and stable piezoelectric performance at extremely low temperatures. Summary of the invention

[0006] To solve the above problems, the present invention provides a potassium sodium niobate-based piezoelectric ceramic suitable for low-temperature environments and a preparation method thereof, which exhibits stable and excellent piezoelectric constants, electromechanical coupling coefficients, and quality factors at room temperature and low temperature ranges, that is, the rate of change of the piezoelectric constant is less than 25%, the rate of change of the electromechanical coupling coefficient is less than 10%, and the rate of change of the quality factor is less than 5%, and does not contain lead elements, and is an environmentally friendly material.

[0007] To achieve the above object, the present invention provides a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment. The potassium sodium niobate-based piezoelectric ceramic is prepared by doping Sb into potassium sodium niobate ceramic. 5+ ,Bi 0.5 Ag 0.5 ZrO3 and NaSbO3 are chemically doped, and then Fe2O3 is added as a sintering aid to form the product. Its general chemical formula is: (0.984-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-xBi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3, where x is Bi 0.5 Ag 0.5 Mole percentage of ZrO3.

[0008] Preferably, x=0.02-0.05; and the molar percentage of antimonate NaSbO3 is 0.016; according to the electric price balance, the component (0.948-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 The atomic ratios of K, Na, Nb, Sb and O in O3 are 0.48, 0.52, 0.95, 0.05 and 3 respectively; the components (Bi 0.5 Ag 0.5 )The atomic ratios of Bi, Ag, Zr and O in ZrO3 are 0.5, 0.5, 1 and 3 respectively; the molar percentage of Fe2O3 is 0.4%.

[0009] A method for preparing potassium sodium niobate-based piezoelectric ceramics suitable for low-temperature environments comprises the following steps:

[0010] S1. Ingredients:

[0011] According to the molar percentage, analytically pure Na2CO3, K2CO3, Nb2O5, Sb2O3, Bi2O3, Ag2O, ZrO2, Fe2O3 are used as raw materials, and the general preparation chemical formula is: (0.984-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-xBi 0.5 Ag 0.5 Weigh the above raw materials in the required stoichiometric ratio for the ZrO3-0.016NaSbO3-0.4%Fe2O3 system;

[0012] S2, ball milling:

[0013] The raw materials obtained in step S1 are ball-milled and dried to obtain a uniformly mixed powder;

[0014] S3, pre-burning the powder obtained in step S2 to obtain dry powder;

[0015] S4, preparing a ceramic body: adding a polyvinyl alcohol aqueous solution to the dry powder, and then sequentially performing granulation, pressing and debinding to obtain a ceramic body;

[0016] S5, sintering the ceramic body to obtain a piezoelectric ceramic body;

[0017] S6. Silver electrodes are applied to the piezoelectric ceramic body, and voltage is applied for polarization.

[0018] Preferably, in step S2, grinding balls and anhydrous ethanol are added to the raw materials, and the raw materials are rolled and milled in a ball mill to obtain powder.

[0019] Preferably, the ball mill jar is a nylon jar, and the grinding balls are zirconium balls.

[0020] Preferably, in step S3, the powder is placed in a corundum crucible, and the corundum crucible is pre-calcined at 850° C. for 6 hours to obtain dry powder.

[0021] Preferably, step S4 specifically includes the following steps:

[0022] S41, adding a polyvinyl alcohol aqueous solution to the dry powder, and granulating the dry powder to obtain a powder;

[0023] S42. Use an electric tablet press to press the powder into round tablets.

[0024] Preferably, in step S41, the mass percentage of the polyvinyl alcohol aqueous solution is 6wt% to 8wt%;

[0025] In step S42, the pressure of the electric machine is 10MPa.

[0026] Preferably, in step S5, the ceramic body is sintered at 1070-1090° C. for 3 hours to obtain a piezoelectric ceramic body.

[0027] Preferably, step S6 specifically includes the following steps: silver electrodes are applied to the piezoelectric ceramic body, and the piezoelectric ceramic body is polarized at 3-4 kV / cm for 10-20 minutes in silicone oil using a withstand voltage tester.

[0028] The present invention has the following beneficial effects:

[0029] 1. In this ceramic, Sb 5+ ,Bi 0.5 Ag 0.5 Both ZrO3 and NaSbO3 have the function of adjusting the phase transition temperature, and can also be adjusted by adjusting Bi 0.5 Ag0.5 The molar percentage of ZrO3 is adjusted to regulate its phase change and dispersion characteristics, and the phase structure regulation in the range of room temperature to extremely low temperature (temperature range is -40 ~ 50 ° C) is realized, and the piezoelectric performance in this temperature range is optimized, and the piezoelectric constant, electromechanical coupling coefficient, and quality factor are stable and excellent in the room temperature and low temperature range, that is, the change rate of the piezoelectric constant is less than 25%, the change rate of the electromechanical coupling coefficient is less than 10%, and the change rate of the quality factor is less than 5%, so it can be applied to electronic sensor equipment in high-cold areas;

[0030] 2. The use of Fe2O3 sintering aid can promote the sintering performance of ceramics, improve the density of ceramics, and help to obtain high-quality ceramics;

[0031] 3. It does not contain lead elements and is an environmentally friendly material, which is beneficial to environmental protection and sustainable development and conforms to the current development trend of the international community;

[0032] 4. The process is simple and stable, easy to operate, and convenient for industrial production.

[0033] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a flow chart of a method for preparing potassium sodium niobate-based piezoelectric ceramics suitable for low-temperature environments according to the present invention;

[0035] Figure 2 is an X-ray diffraction pattern of the piezoelectric ceramic material according to an embodiment of the present invention;

[0036] Figure 3 Schematic diagram of the change of the dielectric constant of the piezoelectric ceramic material according to the embodiment of the present invention with the temperature (-120 to 200° C.); wherein, Figure 3 (a) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 1 with temperature (-120 to 200° C.); Figure 3 (b) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 2 with temperature (-120 to 200° C.); Figure 3 (c) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 3 with temperature (-120 to 200° C.); Figure 3 (d) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 4 with temperature (-120 to 200° C.);

[0037] Figure 4 Schematic diagram of the change of dielectric constant of piezoelectric ceramic material with temperature (50-350° C.) according to an embodiment of the present invention; wherein, Figure 4(a) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 1 with temperature (50-350° C.); Figure 4 (b) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 2 with temperature (50-350° C.); Figure 4 (c) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material described in Example 3 with temperature (50-350° C.); Figure 4 (d) is a schematic diagram showing the change of the dielectric constant of the piezoelectric ceramic material according to Example 4 with temperature (50-350° C.);

[0038] Figure 5 is a schematic diagram showing the variation of the piezoelectric constant of the piezoelectric ceramic material according to an embodiment of the present invention with temperature;

[0039] Figure 6 is a schematic diagram showing the change of the mechanical quality factor of the piezoelectric ceramic material according to an embodiment of the present invention with temperature;

[0040] Figure 7 It is a schematic diagram of the change of the quality factor of the piezoelectric ceramic material according to the embodiment of the present invention with temperature. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention clearer, the embodiments of the present invention are further described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application. Examples of the embodiments are shown in the accompanying drawings, where the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions.

[0042] It should be noted that the terms "include", "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or server comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or devices.

[0043] Like reference numerals and letters denote similar items in the following drawings, and thus, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0044] A potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environments. The potassium sodium niobate-based piezoelectric ceramic is prepared by doping Sb into potassium sodium niobate ceramics. 5+ ,Bi0.5 Ag 0.5 ZrO3 and NaSbO3 are chemically doped, and then Fe2O3 is added as a sintering aid to form the product. Its general chemical formula is: (0.984-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-xBi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3, where x is Bi 0.5 Ag 0.5 The molar percentage of ZrO3 is x = 0.02-0.05; and the molar percentage of antimonate NaSbO3 is 0.016. When the ratio deviates from this ratio, the phase structure and domain structure will change, thereby affecting the piezoelectric performance; according to the electric charge balance, the component (0.948-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 The atomic ratios of K, Na, Nb, Sb and O in O3 are 0.48, 0.52, 0.95, 0.05 and 3 respectively. Otherwise, when the ratio changes, its phase structure will also change, resulting in a decrease in its piezoelectric performance. 0.5 Ag 0.5 ) The atomic ratios of Bi, Ag, Zr and O in ZrO3 are 0.5, 0.5, 1 and 3 respectively. Otherwise, when the ratio changes, its phase structure will also change, resulting in a decrease in its piezoelectric performance. The molar percentages of all the above components or atomic contents are extremely deviated from the ratio, and the excess elements are likely to form impurity phases during the doping process, resulting in a decrease in piezoelectric performance; the molar percentage of Fe2O3 is 0.4%. If the molar percentage of Fe2O3 exceeds 0.4%, it is easy to cause excessive iron elements to form impurity phases and remain in the ceramic structure, resulting in a decrease in piezoelectric performance; if the molar percentage of Fe2O3 is less than 0.4%, the content of the sintering aid is very low, which is easy to make the sintering temperature high, resulting in an increase in production costs, and on the other hand, the promotion effect on sintering is limited, which is easy to lead to poor density of piezoelectric ceramic materials, which is not conducive to improving piezoelectric performance.

[0045] It should be noted that the “-” in the general formula represents a uniform compound formed by doping multiple components.

[0046] The principle is: using Sb element, zirconate (Bi 0.5 Ag 0.5 )ZrO3, antimonate NaSbO3, chemical modification, optimization of piezoelectric properties, and then by adjusting (Bi 0.5 Ag 0.5)ZrO3 content, further adjust the phase structure and dispersion characteristics at low temperature. And with (Bi 0.5 Ag 0.5 ) With the increase of ZrO3 content, the trigonal-orthogonal phase transition temperature increases, and the orthogonal-tetragonal phase transition temperature decreases, which makes the R phase gradually decrease and the O phase gradually increase in the room temperature and low temperature range. At the same time, its local field gradually increases, resulting in a decrease in the size of the ferroelectric domain, an increase in the dispersion characteristics, a decrease in the polarization barrier, and thus an improvement in the piezoelectric properties of the piezoelectric ceramic material.

[0047] A method for preparing potassium sodium niobate-based piezoelectric ceramics suitable for low-temperature environments comprises the following steps:

[0048] S1. Ingredients:

[0049] According to the molar percentage, analytically pure Na2CO3 (sodium carbonate), K2CO3 (potassium carbonate), Nb2O5 (niobium pentoxide), Sb2O3 (antimony trioxide), Bi2O3 (bismuth oxide), Ag2O (silver oxide), ZrO2 (zirconium oxide), and Fe2O3 (iron trioxide) are used as raw materials. The general chemical formula for preparation is: (0.984-x)K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-xBi 0.5 Ag 0.5 Weigh the above raw materials in the required stoichiometric ratio for the ZrO3-0.016NaSbO3-0.4%Fe2O3 system;

[0050] S2, ball milling:

[0051] The raw materials obtained in step S1 are ball-milled and dried to obtain a uniformly mixed powder;

[0052] In step S2, grinding balls and anhydrous ethanol are added to the raw materials, and the raw materials are rolled and milled in a ball mill to obtain powder. The ball mill is a nylon mill and the grinding balls are zirconium balls.

[0053] S3, pre-burning the powder obtained in step S2 to obtain dry powder;

[0054] In step S3, the powder is put into a corundum crucible, and the corundum crucible is pre-fired at 850° C. for 6 hours to obtain dry powder.

[0055] S4, preparing a ceramic body: adding a polyvinyl alcohol aqueous solution to the dry powder, and then sequentially performing granulation, pressing and debinding to obtain a ceramic body;

[0056] Step S4 specifically includes the following steps:

[0057] S41, adding a polyvinyl alcohol aqueous solution to the dry powder, and granulating the dry powder to obtain a powder;

[0058] S42. Use an electric tablet press to press the powder into round tablets.

[0059] In step S41, the mass percentage of the polyvinyl alcohol aqueous solution is 6wt% to 8wt%. If the added polyvinyl alcohol aqueous solution is less than 6wt%, the sample is likely to be unformed and the piezoelectric ceramic material cannot be obtained. If it is higher than 8wt%, the piezoelectric performance is likely to be reduced or the sample has holes, resulting in the inability to obtain a dense piezoelectric ceramic material. In this embodiment, the content of the polyvinyl alcohol aqueous solution is preferably 8wt%.

[0060] In step S42, the pressure of the electric machine is 10MPa.

[0061] S5, sintering the ceramic body to obtain a piezoelectric ceramic body;

[0062] In step S5, the ceramic body is sintered at 1070-1090° C. for 3 hours to obtain a piezoelectric ceramic body.

[0063] S6. Silver electrodes are applied to the piezoelectric ceramic body, and voltage is applied for polarization.

[0064] Step S6 specifically includes the following steps: silver electrodes are applied to the piezoelectric ceramic body, and the piezoelectric ceramic body is polarized at 3-4 kV / cm for 10-20 minutes in silicone oil using a withstand voltage tester.

[0065] In order to better understand the technical solution provided by the present invention, the following embodiments are disclosed:

[0066] Example 1

[0067] In the chemical formula of potassium sodium niobate based piezoelectric ceramics, x is selected as 0.02, and its chemical formula is: 0.964K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-0.02Bi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3;

[0068] The method for preparing the potassium sodium niobate-based piezoelectric ceramic is as follows:

[0069] The first step is to use analytically pure Na2CO3, K2CO3, Nb2O5, Sb2O3, Bi2O3, Ag2O, ZrO2, and Fe2O3 as raw materials and weigh each raw material according to molar percentage;

[0070] Step 2: Use anhydrous ethanol as the ball milling medium to grind the weighed raw materials, and then roll the mill for 24 hours and dry them to obtain a mixed dry powder;

[0071] Step 3: Keep the obtained dry powder at 850°C for 6 hours;

[0072] Step 4: Add 8 wt% polyvinyl alcohol aqueous solution to the pre-burned powder for granulation; after granulation, use a 10 mm diameter mold to press into small discs at a pressure of 10 MPa, with a diameter of 10 mm and a thickness of 1 mm, and glue side by side;

[0073] Step 5: Sinter the debinded small discs at different temperatures and different holding times to obtain ceramic sheets;

[0074] Step 6: The sintered ceramic sheet is coated with silver electrodes and polarized in silicone oil at a voltage of 4 kV / mm for 30 minutes;

[0075] Step 7: After the polarized ceramic sheet is left to stand in the air for 24 hours, the electrical performance is tested at room temperature and low temperature using the IEEE standard.

[0076] Example 2

[0077] In the chemical formula of potassium sodium niobate-based piezoelectric ceramics, x is selected as 0.03, and its chemical formula is: 0.954K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-0.03Bi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3;

[0078] The method for preparing the potassium sodium niobate-based piezoelectric ceramic is similar to the method for preparing the same in Example 1. The difference is that the molar ratio of the raw materials is weighed and prepared according to the chemical formula in Example 2.

[0079] Example 3

[0080] In the chemical formula of potassium sodium niobate based piezoelectric ceramics, x is selected as 0.04, and its chemical formula is: 0.944K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3;

[0081] The method for preparing the potassium sodium niobate-based piezoelectric ceramic is similar to the method for preparing the same in Example 1. The difference is that the molar ratio of the raw materials is weighed and prepared according to the chemical formula in Example 3.

[0082] Example 4

[0083] In the chemical formula of potassium sodium niobate-based piezoelectric ceramics, x is selected as 0.05, and its chemical formula is: 0.934K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3-0.05Bi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3;

[0084] The method for preparing the compound having the general chemical formula: is similar to the method for preparing the compound in Example 1. The difference is that the molar ratio of the raw materials is weighed and prepared according to the chemical formula in Example 4.

[0085] like Figure 2 As shown, the characteristic peaks between 20-70° are:

[100] ,

[110] ,

[002] ,

[200] ,

[210] ,

[211] ,

[220] , indicating that the potassium sodium niobate-based piezoelectric ceramic is a perovskite ceramic. Split peaks appear near 45-46°, and the peak intensity ratio deviates from 1:2 or 2:1, indicating that the potassium sodium niobate-based piezoelectric ceramic presents a multi-phase coexistence structure.

[0086] like Figure 3 As shown, the piezoelectric ceramics of Example 1 and Example 2 have two dielectric peaks, corresponding to the "trigonal-orthogonal" and "orthogonal-tetragonal" phase transitions. The "trigonal-orthogonal" phase transition occurs near 0°C and has an obvious dispersion phenomenon. The phase transition temperature range can reach -50 to 30°C, while the "orthogonal-tetragonal" phase transition temperature is 100°C and 80°C, respectively, which is much higher than room temperature. 0.5 Ag 0.5 As the ZrO3 content increases further, the orthorhombic-tetragonal phase transition temperature of the piezoelectric ceramic of Example 3 further decreases, gradually overlapping with the trigonal-orthorhombic phase transition region, and presenting a "trigonal-orthorhombic-tetragonal" phase boundary near room temperature. The ceramic of Example 4 presents a "trigonal-orthorhombic-tetragonal" phase boundary with significantly enhanced dispersion.

[0087] like Figure 4 As shown in the figure, the highest point of the dielectric peak is caused by the "tetragonal-cubic" phase transition, and the corresponding temperature is the Curie temperature. 0.5 Ag 0.5 As the ZrO3 content increases, the Curie temperature gradually decreases. The Curie temperatures of Examples 1-4 are 230°C, 214°C, 188°C and 137°C, respectively. It can be seen that they are all much higher than room temperature.

[0088] like Figure 5-Figure 7 As shown, with Bi 0.5 Ag 0.5As the ZrO3 content increases, its piezoelectric constant gradually increases, and the performance degradation trend caused by decreasing temperature gradually weakens. 0.5 Ag 0.5 The increase of ZrO3 content shows a trend of increasing first and then decreasing, but the temperature stability gradually increases. The quality factor shows a downward trend, but its temperature stability is significantly enhanced.

[0089] Therefore, the present invention adopts the above-mentioned potassium sodium niobate-based piezoelectric ceramics suitable for low-temperature environments and the preparation method thereof, which exhibit stable and excellent piezoelectric constants, electromechanical coupling coefficients, and quality factors at room temperature and low temperature ranges, that is, the change rate of the piezoelectric constant is less than 25%, the change rate of the electromechanical coupling coefficient is less than 10%, and the change rate of the quality factor is less than 5%, and does not contain lead elements, and is an environmentally friendly material.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environments, characterized in that: Potassium sodium niobate-based piezoelectric ceramics are prepared by doping Sb into potassium sodium niobate ceramics. 5+ , Bi 0.5 Ag 0.5 ZrO3 and NaSbO3 are chemically doped, and then Fe2O3 is added as a sintering aid to form the product. Its general chemical formula is: (0.984- x )K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3- x Bi 0.5 Ag 0.5 ZrO3-0.016NaSbO3-0.4%Fe2O3, among which x for Bi 0.5 Ag 0.5 The molar percentage of ZrO3, x = 0.02-0.05; and the molar percentage of antimonate NaSbO3 is 0.016; according to the balance of electricity price, the components (0.948- x )K 0.48 Na 0.52 Nb 0.95 Sb 0.05 The atomic ratios of K, Na, Nb, Sb and O in O3 are 0.48, 0.52, 0.95, 0.05 and 3 respectively; the components (Bi 0.5 Ag 0.5 )The atomic ratios of Bi, Ag, Zr and O in ZrO3 are 0.5, 0.5, 1 and 3 respectively; the molar percentage of Fe2O3 is 0.4%.

2. A method for preparing a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environments as claimed in claim 1, characterized in that: The following steps are involved: S1. Ingredients: According to the molar percentage, analytically pure Na2CO3, K2CO3, Nb2O5, Sb2O3, Bi2O3, Ag2O, ZrO2, Fe2O3 are used as raw materials, and the general preparation chemical formula is: (0.984- x )K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3- x Bi 0.5 Ag 0.5 Weigh the above raw materials in the required stoichiometric ratio for the ZrO3-0.016NaSbO3-0.4%Fe2O3 system; S2, ball milling: The raw materials obtained in step S1 are ball-milled and dried to obtain a uniformly mixed powder; S3, pre-burning the powder obtained in step S2 to obtain dry powder; S4, preparing a ceramic body: adding a polyvinyl alcohol aqueous solution to the dry powder, and then sequentially performing granulation, pressing and debinding to obtain a ceramic body; S5, sintering the ceramic body to obtain a piezoelectric ceramic body; S6. Silver electrodes are applied to the piezoelectric ceramic body, and voltage is applied for polarization.

3. The method for preparing a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment according to claim 2, characterized in that: In step S2, grinding balls and anhydrous ethanol are added to the raw materials, and the raw materials are rolled and milled in a ball mill to obtain powder.

4. The method for preparing a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment according to claim 3, characterized in that: The ball mill jar is a nylon jar and the grinding balls are zirconium balls.

5. The method for preparing a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment according to claim 2, characterized in that: In step S3, the powder is put into a corundum crucible, and the corundum crucible is pre-fired at 850° C. for 6 hours to obtain dry powder.

6. The method for preparing a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment according to claim 2, characterized in that: Step S4 specifically includes the following steps: S41, adding a polyvinyl alcohol aqueous solution to the dry powder, and granulating the dry powder to obtain a powder; S42. Use an electric tablet press to press the powder into round tablets.

7. The method for preparing a potassium sodium niobate-based piezoelectric ceramic suitable for low temperature environment according to claim 6, characterized in that: In step S41, the mass percentage of the polyvinyl alcohol aqueous solution is 6wt%~8wt%; In step S42, the pressure of the electric tablet press is 10 MPa.

8. The method for preparing potassium sodium niobate-based piezoelectric ceramics suitable for low temperature environments according to claim 2, characterized in that: In step S5, the ceramic body is sintered at 1070-1090° C. for 3 hours to obtain a piezoelectric ceramic body.

9. The method for preparing potassium sodium niobate-based piezoelectric ceramics suitable for low temperature environments according to claim 2, characterized in that: Step S6 specifically includes the following steps: silver electrodes are applied to the piezoelectric ceramic body, and the piezoelectric ceramic body is polarized at 3-4 kV / cm for 10-20 minutes in silicone oil using a withstand voltage tester.

Citation Information

Patent Citations

  • Potassium-sodium niobate-based leadless piezoelectric ceramic and preparation method thereof

    CN111302797A

  • High-voltage anti-fatigue potassium niobate sodium based leadl-free piezoelectric ceramic and preparation method thereof

    CN113461422A